How to stimulate supplier innovation? Insights from a multiple case study. Issue 3 (June 2019) - Pihlajamaa, Matti; Kaipia, Riikka; Aminoff, Anna; Tanskanen, Kari
Abstract: Drawing on the literature on supplier innovation, supplier development, and the relational view, we bring forward the concept of stimulation of supplier innovation, which refers to the buyer company's actions which aim to enhance its suppliers' innovativeness, guide its suppliers' innovation processes, and/or encourage its suppliers to share their innovations. Through four case studies about purchasing categories in three companies, we study how the stimulation focus is determined and what methods can be used for stimulating supplier innovation. We propose that stimulation comprises indirect and direct forms of knowledge-sharing and governance with an emphasis on indirect methods and suggest that the concept sheds light on the research gap on the push model of supplier innovation. We also elaborate the literature on supplier development and relational view in the context of supplier innovation. Highlights: Proposes the concept of the stimulation of supplier innovation. Identifies three conditions for a buyer to benefit from its suppliers' innovativeness. Stimulation comprises a combination of knowledge-sharing routines and effective governance. Stimulation has an emphasis on indirect methods that rely on the suppliers' voluntary actions.